Modification of English Complex Noun Phrases: A Case Study of Native and Non-Native Writers - Rika Mutiara (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
This study aims at examining differences of complex noun phrases written by Indonesian writers and English native writers in English academic prose particularly undergraduate students’ theses. The complex noun phrases were scrutinized based on how they were modified (Biber, Johansson, Leech, Conrad, & Finegan, 1999, pp.588-644). Corpus method that is concordance analysis of nouns was applied to identify the modifications. The data were taken from four undergraduate theses. Two of them were written by non-native writers and the others were produced by native writers. The differences cover some modifiers namely adverb (phrase) as premodifiers and postmodifiers, adjective (phrase) as postmodifiers, relativizers, prepositional phrases, appositives, and multiple modifiers whether premodifiers or postmodifiers. The differences occur might be caused by L1 interference such as in the use of adjective (phrase), adverb phrase, and reflexive pronoun as postmodifier. Non-native writers do not produce any adjective (phrase) and reflexive pronoun as postmodifiers. For multiple premodifiers and postmodifiers, differences occur in the form of the highest number of modifiers in the NPs and their types. In the long noun phrases, the non-native writers modified the nouns with a number of appositives. NPs written by native writers of English are more complex.